Penyuluhan mengenai bahaya "Kecacingan" di TPA Al Ikhlas Polri, Jatisampurna, Bekasi - Intan Kurniawati Pramitaningrum; Septiani Septiani; Muhammad Rizki Kurniawan (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
Worms infection disease is a health problem often found in the world and Indonesia. Worms’ infection disease commonly found in Indonesia and which infected children are caused by Ascaris lumbricoides, Trichuris Trichiura, and Enterobius vermicularis. One of the children affected by worms is often playing with the ground because of the habit. Al Ikhlas School’s Polri in Jatisampurna Bekasi consists of pre-primary and elementary schools that have never received counseling about the dangers of worms’ infection. This activity aims to educate children about the dangers of worms’ infection. The method used is through filling out questionnaires, counseling, media posters, and handwashing demonstrations. The activity was attended by 21 with 81% had experienced worms’ infection disease and 19% had never have experienced worms’ disease, and 85,71 % understood about knowledge of worms’ infection disease and 14,29 did not understand. The counseling provided included egg and adult worms, the cause of worms’ disease infection, how to get infections, the danger of infection, and prevent infection.